INCREASING WASTEWATER TREATMENT EFFICIENCY USING HYDROBIONTS - D. B. Bozorova (Web of Journals Publishing, 2025)
This article is focused on wastewater treatment using hydrobionts and was conducted in the Bukhara water supply. As a result, in order to ensure the activity of microorganisms in the treatment plant and increase the efficiency of high purification, it was achieved to ensure that the oxygen content in the aeration tank was not lower than 4.6 mg/l and the IL index was not lower than 150 mg/l. It was recommended to use the treated wastewater for irrigation of technical crops and ornamental plants
Keywords: Wastewater, hydrobionts, treatment, seriobacteria, Infusoria.